Nutritional Evaluation of Whole and Lipid-Extracted Biomass of the Microalga Scenedesmus sp. AMDD for Animal Feeds: Simulated Ruminal Fermentation and In Vitro Monogastric Digestibility - M. Tibbetts, Sean; H. Fredeen, Alan (Current Biotechnology, 2017)
Background: Scenedesmus sp. AMDD (S-AMDD) has been the focus of several studies to assess its potential as a feedstock for biofuels and bioremediation, while the evaluation of its potential suitability as a novel animal feed ingredient has only just begun. In an initial study, S-AMDD demonstrated rapid growth rate and biomass productivity during exponential growth phase and the resulting biomass appeared to have good potential for animal nutrition based on its attractive proximate composition, favorable essential amino acid, fatty acid and elemental profiles and lack of contaminating heavy metals. However, the total carbohydrate and fibre fractions of whole-cell and lipid-extracted S-AMDD were relatively high which could limit their digestion, particularly when fed to monogastric animals. The difference in the capacity to digest and metabolically utilize diets rich in cellulosic material (e.g., fibre) is vast between various farmed animal species. As such, knowledge on the nutritional value of novel ingredients for ruminant animals can rarely be immediately extrapolated to monogastrics and vice versa. Simulated fermentation using rumen-derived digestive fluids or in vitro digestibility using purified monogastric- derived enzymes can provide valuable information. Although not fully conclusive, results from these types of rapid assays are generally inexpensive, require smaller amounts of sample, utilize fewer or no experimental animals, avoid feed refusal issues associated with ingredient off-flavours or odours and can be effective tools for research and for routine industrial use. Objective: The present study is the second in a series of projects designed to evaluate the nutritional value of S-AMDD for animal feed applications. The main objective was to generate novel digestibility data of whole-cell and lipid-extracted S-AMDD for both ruminant and monogastric animals including ruminal organic matter digestibility (OMD), apparent metabolizable energy (aME) content, methane (CH4) production, dilute pepsin digestibility (DPD) and two-phase gastric/pancreatic digestibility of protein (GPDProtein) and energy (GPDEnergy). Methods: Simulated ruminal OMD, aME contents and CH4 production of experimental test diets containing graded levels of whole-cell and lipid-extracted S-AMDD were estimated using a modified batchculture in vitro fermentation system with total gas capture using lactating dairy cattle as rumen fluid donors. In vitro monogastric DPD and two-phase GPD were measured by incubation of whole-cell and lipid- extracted S-AMDD samples in porcine pepsin and porcine pancreatin, containing amylase, lipase and protease enzyme solutions. Results: Simulated ruminal fermentations using lactating dairy cattle as rumen fluid donors indicate that both whole-cell and lipid-extracted S-AMDD have excellent potential for use in ruminant animal feeds. Dietary inclusion of whole-cell S-AMDD at 50% forage protein replacement (equivalent to 20% of the total diet) or lipid-extracted S-AMDD at 100% forage protein replacement (equivalent to 32% of the total diet) did not significantly affect OMD or aME content of the control diet. However, OMD was marginally compromised with 100% forage protein replacement with whole-cell S-AMDD (equivalent to 40% of the total diet) relative to the 25 and 50% replacement levels, although not significantly different from the control diet. Diets containing lipid-extracted S-AMDD significantly reduced CH4 production by approximately 50% compared to the control diet (47% reduction) and those containing whole-cell SAMDD (51% reduction). Since OMD and aME content of diets containing lipid-extracted S-AMDD were unaffected relative to the control diet and whole-cell S-AMDD-containing diets, it seems clear that lipid-extracted S-AMDD contains anti-methanogenic ‘non-fatty acid' substances that have the ability to suppress rumen methanogenic bacteria without disturbing ruminal digestion. This area warrants further exploration in vivo, especially considering the large volume of algal feed that could be produced without occupying significant land resources. In vitro monogastric digestibility using porcine enzymes indicates that lipid-extracted S-AMDD has potential for use in monogastric animal feeds. Protein and energy digestibility of this product were moderately high (75-84% and 70%, respectively), which resulted in relatively high contents of DP (30%) and DE (14 MJ kg-1). On the other hand, the digestibility of whole-cell S-AMDD was low at 52-61% and 50%, respectively resulting in lower levels of DP (15%) and DE (12 MJ kg-1). Despite the encouraging results for lipid-extracted S-AMDD, the digestibility (particularly of energy) remains marginal for monogastric animals and requires improvement through additional cost-effective cell rupture technologies or the production of algal protein concentrates..
Keywords: monogastric